Study of the effects of radiofrequency in facial treatment in women aged between 30 and 50 years (Research, Society and Development, 2022)
Facial aging affects the skin, causing functional and morphological, permanent and irreversible changes due to the low production of collagen and elastin fibers from the age of 25, becoming accentuated from the age of 40. Exposure to the sun, stress, bad habits (smoking and excessive alcohol consumption), environmental pollution, poor diet, vitamin deficiency, lead to the appearance of fine lines and sagging skin. The advancement of technology makes it possible to delay facial aging, such as radiofrequency, which is a painless and non-invasive technology, capable of acting on the skin and subcutaneous layers, promoting the activation of fibroblasts to produce collagen and elastin fibers, through an inflammatory process. controlled, improving tissue sagging and expression lines. Objective: to analyze the possible effects of bipolar radiofrequency on the face. Methodology: the work is characterized by experimental research with weekly sessions following the protocol and manufacturer's specifications. Five volunteers selected by inclusion criteria participated in the research, being women between 30 and 50 years old, with fair skin and high facial sagging. Results: All volunteers had a satisfactory result. It is possible to notice improvements in hydration, reduction of expression marks. 80% of the volunteers did not complain of discomfort during the sessions. Conclusion: Radiofrequency is an indicated and safe alternative for aesthetic purposes. The action of the treatment causes the stimulation of collagen fibers, promoting improvements in the deep hydration of the skin, facial rejuvenation, improvements in the appearance and appearance and softening of lines and expression marks.